Neuronal regulation of Gram-negative bacterial pneumonia and host defense - Joshi, Prabhu Raj (My University, 2026)
The nervous and immune systems interact closely to maintain tissue homeostasis. The neuroimmune crosstalk can play a beneficial or detrimental role in infections, depending on the types of pathogens and the organ system involved. In the lung, neural pathways regulate respiratory physiology and immune responses during infections. However, the mechanisms by which different neuronal populations regulate lung immunity during bacterial pneumonia remain poorly understood. This dissertation research investigates the roles of sensory and [beta]₂-adrenergic receptor ([beta]₂-AR) signaling during Gram-negative bacterial pneumonia and sepsis. Using murine models of lung infection with the extracellular pathogen Klebsiella pneumoniae and the intracellular pathogen Burkholderia thailandensis, this work demonstrates that distinct neural pathways differentially regulate antibacterial immunity. In the second chapter, lung-innervating nociceptor sensory neurons (or nociceptors) were found to impair host defense during carbapenem-resistant K. pneumoniae (CRKP) infection. Ablation of nociceptors enhanced bacterial clearance, reduced dissemination of CRKP to extrapulmonary organs, and improved survival. These protective effects were associated with increased recruitment of Ly6C[superscript hi] monocytes into the airways. Mechanistically, the nociceptor-released neuropeptide calcitonin gene-related peptide (CGRP) suppressed reactive oxygen species production in recruited Ly6C[superscript hi] monocytes, thereby limiting their antibacterial immunity. In the third chapter, the [beta]₂-AR signaling pathway was shown to promote host defense against Burkholderia thailandensis infection. Mice lacking [beta]₂-AR exhibited impaired bacterial clearance, exaggerated lung inflammation, promoted severe sepsis, and increased mortality. In contrast, pharmacological activation of [beta]₂-AR improved survival, enhanced bacterial clearance, increased immune cell recruitment, and reduced inflammatory cytokine production. Furthermore, [beta]₂-AR signaling enhanced macrophage-mediated intracellular bacterial killing through increased nitric oxide production. Together, these findings reveal that neuroimmune signaling is a critical regulator of antibacterial immunity in the lung. Nociceptor-derived CGRP impairs host defense against extracellular bacteria; however, [beta]₂-AR signaling mediates host defense against intracellular bacterial infections. This work advances understanding of neuroimmune regulation in the lung and identifies neural pathways as potential therapeutic targets for severe bacterial pneumonia and sepsis.
Keywords: Bacterial pneumonia; Sepsis; Lungs; Neuroimmunology